Gestão democrática da escola pública e participação popular: uma análise sobre o sistema municipal de ensino do município de João Pessoa-PB - Santos, Laurineide Laureano dos (2011)
This study aims to examine the implementation of democratic management in the public schools of the city of João Pessoa - Paraiba, from the deployment of spaces and participatory mechanisms provided for in the Municipal System of Education - SME, seeking to understand the limits and possibilities of Democratic Management, to be adopted both as a theoretical literature about the democratic management of public schools, popular education, participation, school administration, national and local education laws, based on the qualitative method, but resorting to strategies employed in multimetodológicas quantitative and qualitative research, and used as instruments of data collection the questionnaire with open and closed questions and the technique of participant observation accompanied by a diary. The analysis of the implementation of mechanisms and opportunities for participation by schools shows how the concrete possibilities of democratic management, the implementation of mechanisms and opportunities for participation, with the absence of limits on participation of students in the Class Councils, the lack of service employees and secretary general and parents in planning meetings and teaching and the absence of the local community in the deliberative councils School. We conclude that democratic management is being implemented, but the participation of school and local community is not taking place in its fullness.